Gleichstellungspolitik an Hochschulen Was wissen und wie handeln Professorinnen und Professoren? - Klammer, Ute (Verlag Barbara Budrich, 2020)
What knowledge do professors have about gender and equality issues and how do they implement equality in their key areas of activity - as managers in research, teaching and academic self-administration? The aim of the volume is to shed light on the interaction of the knowledge and attitudes of professors on the one hand and their action orientations with regard to equality on the other .